ELECTROPHYSICAL PROPERTIES OF CONTACTS WITH IRSI – SI SCHOTTKY BARRIER - E. A. Kerimov (Вестник Кемеровского государственного университета, 2013)
Holes in N2 atmosphere were detected on the IrSi surface, obtained by magnetron spraying, the same defects are observed in IrSi, obtained by method of thermal evaporation in vacuum. The decrease in defects size by annealing in a N2 + H2 + O2 gas mixture is due to iridium decomposing the neutral hydrogen atoms, which in turn interact with the adsorbed oxygen, and are further desorbed or replaced to the silicon surface by temperature increasing.